Pengaruh Brand Image Dan Online Customer Review Terhadap Keputusan Pembelian Produk Skintific (Studi Pada Konsumen Produk Skintific Di Kota Medan) - Muhammad Daffa Aqila; Feby Aulia Safrin; Onan Marakali Siregar (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The skincare industry in Indonesia has been rapidly growing along with increasing public awareness of skin health. In a highly competitive market, brand image and online customer reviews are crucial factors that influence consumer purchasing decisions. This study aims to analyze the effect of brand image and online customer reviews on purchasing decisions for Skintific products among consumers in Medan City. This research applies a quantitative associative approach with a purposive sample of 100 male respondents aged ≥17 who had purchased Skintific products after reading online reviews. Data were collected using structured questionnaires and analyzed through validity and reliability tests, classical assumption tests, multiple linear regression, partial test (t), simultaneous test (F), and coefficient of determination (R²). The results indicate that brand image (X1) and online customer reviews (X2) have positive and significant effects on purchasing decisions (Y), both partially and simultaneously. Regression coefficients show B_X1 = 0.670 (t = 4.511; p < 0.001) and B_X2 = 0.540 (t = 5.753; p < 0.001). Correlation R = 0.919 and Adjusted R² = 0.842 indicate that 84.2% of purchasing decision variance is explained by these two variables.